‘Steve Bannon is watching us closely’: Naomi Klein on populists, conspiracists and real-world activism - Goodfellow, Maya (The Guardian, 2023)
Author speaks candidly about a ‘mirror world’ that feeds our anxieties, distorts reality and fuels the polarisation of society
Keywords: 2023-10 October; Books; Climate crisis; Culture; Environment; Naomi Klein; Naomi Wolf; Steve Bannon; The far right; US news; World news